Public food procurement for sustainable food systems and healthy diets - Volume 2 - Swensson, Luana; Hunter, Danny; Schneider, Sergio; Tartanac, Florence (Food and Agriculture Organization of the United Nations, 2021)
Sustainable Public Food Procurement (PFP) represents a key game changer for food systems transformation. It can influence both food consumption and food production patterns. It can deliver multiple social, economic and environmental benefits towards sustainable food systems for healthy diets. This publication aims to contribute to the improved understanding, dissemination and use of PFP as a development tool in particular in the case of school meals programmes. In this Volume 2, researchers, policymakers and development partners can find extensive evidence of the instruments, enablers and barriers for PFP implementation. It also provides case studies with local, regional and national experiences from Africa, Asia, Europe and North and South America.